P‐119: Low Cost Perovskite Quantum Dots Film Based Wide Color Gamut Backlight Unit for LCD TVs. Issue 1 (30th May 2018) - Chen, Naijun; Bai, Zelong; Wang, Zengmin; Ji, Honglei; Liu, Ruikuo; Cao, Chaowei; Wang, Hui; Jiang, Feng; Zhong, Haizheng
Abstract : Perovskite quantum dots film exhibits low cost, low heavy metal content, high brightness and narrow emission peak. Here, we introduced features of Perovskite quantum dots film and its beneficial effects in LCD TVs applications. Afterwards, we thoroughly compared the Perovskite quantum dots film and CdSe based quantum dots enhancement film.